Assessment of Water and Land Resources Potential for Surface Irrigation Development Using GIS: A Case Study of Akaki River Catchment - Neddi, Johar (ASTU, 2022)
Investigating available land and water resources for irrigation is essential for the development of irrigated agriculture.An assessment of the land and surface water resources potential of Akaki catchment was conducted to alleviate lack of required information in relation to potential irrigable area, available water and irrigation water demand for dominant crops which can help for the planning of irrigation development. This study was initiated with the objective of evaluate the water and land resources potential of Akaki river catchment for irrigation development and generating geo-referenced map of the resources by using Geographic Information System. To meet the main objective of the study, land suitability, available water potential and irrigation water demands were evaluated. The most determinant factors of surface irrigation were land use land cover, slope and soil suitability were assessed.Potentially suitable sites for surface irrigation development was evaluated for each selected Vegetable crops (potato,tomato,cabbage and pepper). Soil suitability was examined in terms of soil depth, texture and drainage for surface irrigation using GIS model and reference evapotranspiration, net effective rainfall,net and gross irrigation requirement or each of the crop was estimated using CROPWAT software. The maximum potentially suitable area of the Akaki catchment is nearly 67.06% (114,939ha), out of which 6.56% (10,570ha) is highly suitable, 28.07% (45,191ha) moderately suitable, about 36.75% (59,178ha) is marginally suitable and the rest 28.62% (46.081ha) is not suitable. The annual average flow of the river was estimated as 26.585Mm3 which has a capacity to irrigate 37,169.61ha of land from total available land potential. The total gross water requirement for all crops (potato, tomato, cabbage and pepper) for available land potential was found as 7.413Mm3. It is evident from the finding that the Total potential irritable land of 114,939 ha required 28.469Mm3 gross irrigation water for the selected crops. This is showed that irrigation water demand is greater than the available stream flow. To curve the problem of shortage of water, it is recommended to implement irrigation water management, using technology, water harvesting structures and exploring water from ground to fully develop the identified irrigation potential in the study area.
Keywords: Surface Irrigation, Land Suitability, GIS, Surface water availability